Translation as Style and Technique in the Hybrid Englishes of Raja Rao’s Kanthapura and Eileen Chang’s Lust, Caution - Iyer, Sreedhevi (SARE: Southeast Asian Review of English, 2019)
The postcolonial writer and the translator of literary works possess similar literary challenges. Both are required to explicate unfamiliar elements from an original cultural source or text in a way that is comprehensible to a contemporary global audience. However, for the postcolonial writer this can amount to a certain didactic quality to the literary work, which is a devalued aesthetic within contemporary literary standards. As such, the writer incorporates translative elements in his creative process to get around the problem. To demonstrate this, I analyze and compare the works of two authors, Raja Rao and Eileen Chang. I argue that Rao’s incorporation of the Kannada language into Kanthapura strategically resists prevailing standards of cultural explication, while Eileen Chang’s initial draft of Lust, Caution, written in English as The Spyring, engages in overt cultural explication that fails to capture the nuances of its translated version. The intentional construct of linguistic and aesthetic permutations in both works can be characterized as an act of translation.